The challenges and opportunities associated with deferred consent in time-sensitive pediatric emergency research: a systematic review - Talukdar, Jhalok Ronjan (My University, 2019)
Introduction Obtaining informed consent is mandatory to involve human subjects in research. Researchers need to provide adequate information to the participants about the study including risks and benefits associated with the study in simple language so that the participants can comprehend the information. Informed consent has to be obtained from parents/guardians if the participants are children under 18. However, it is not feasible to obtain informed consent from parents/guardians in a time-sensitive pediatric emergency. In such situations, the clinicians may need to start the treatment immediately. The researchers often do not have time to provide adequate information to the parents/guardians to take informed consent. The parents may also not be in the right mental space to comprehend this information. Deferred consent is introduced to conduct studies in time-sensitive medical emergencies. It is also used to conduct studies in time-sensitive pediatric medical emergencies. It allows the researchers to enroll children in the study immediately and take consent as early as the health condition of the children is stabilized. Deferred consent is a new phenomenon in time-sensitive pediatric emergency research and there is a lack of evidence regarding the opportunities and challenges associated with this consent model. This review explored the challenges and opportunities associated with the application of this model in time-sensitive pediatric emergency research. Methods Four databases - MEDLINE, EBMASE, CINAHL, and PsycINFO were searched for the articles developing a comprehensive search strategy. The identified articles were deduplicated. The titles and abstracts of these articles were screened, the full-text articles were collected and read for final selection. The selected articles were imported to NVivo 12. These articles were coded using NVivo 12 for thematic analysis of them. The identified themes explored the challenges and opportunities associated with deferred consent. Results The children, parents, and practitioners had positive impressions about deferred consent. They thought using deferred consent would allow the practitioners to start the treatment immediately and would give them enough time to discuss research participation later. However, there were some challenging situations for the practitioners to take deferred consent from the parents. It was difficult for them to understand when the appropriate time is to approach the parents for research discussion. The practitioners were also in a dilemma whether they should approach bereaved parents for deferred consent. They also faced ethical dilemma for collecting extra blood for study purposes only. Moreover, it was also challenging for them to address the concerns of the parents about the study. Conclusion Deferred consent in time-sensitive pediatric emergency research allows the clinicians to recruit the children immediately and take consent from the parents when their health condition is stable. The children, parents and practitioners had support for differed consent. However, it was challenging for the practitioners to find a suitable time to discuss research with the parents. It was difficult for them to approach the bereaved parents for deferred consent. There was a lack of studies on deferred consent especially studies which explored perspectives of children and bereaved parents on deferred consent. More studies on deferred consent in time-sensitive pediatric emergency research will guide future researchers to overcome their ethical dilemma in this situation and contribute more in pediatric emergency medicine.